Dissecting the Humanitarian and Environmental Priority in Global Politics [Membedah Prioritas Kemanusiaan dan Lingkungan dalam Politik Global] - Imanuel, Gloria Miracle Melody; Fani, Guillermo Valles; Supit, Christina Nataysha; Pandie, Nathaniel Henry; Kryzstov, Sean (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2023)
Human rights and environmental issues have come to be one of the most sought-after topics of discussion and endless debates amongst world leaders and citizens of the Earth. Both topics encompass the concepts of freedom, life and survival for all humans who roam the Earth in an equal manner. As of late, the debate regarding human rights and environmental issues is being overshadowed by conflicts between nations, political and economic rivalry, and a progressive inclination away from a united international society. Although it is understandable as to why world governments would prefer to prioritize such topics of concern, human rights violations outside of such topics along with environmental issues like climate change must not be set aside only to be picked up again some other time of convenience. Therefore, we must investigate ways for us to properly understand the scale of severity and utter importance these topics must remain amidst other conflicts. This paper seeks to do just that, by providing material and explanations regarding the topics and reaching the conclusion. The methodology used to research and collect data includes various credible journals and websites as secondary sources while obtaining its primary sources via interviews with credible experts on the topics that will be discussed.